The efficacy of transvaginal ultrasonography and office hysteroscopy in evaluation of abnormal uterine bleeding - Reddy M. R., Sona; Subhashchandra, Mudanur R.; Patil, Neelamma B.; G. Yaliwal, Rajasri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abnormal uterine bleeding (AUB) is a prevalent issue in women of child bearing age group. AUB can be uncomfortable and have a considerable impact on health-related quality of life. AUB is reported to occur in 9 to 14% women between menarche and menopause and reported prevalence in India is around 17.9%. Methods: It is a prospective observational study done in 75 patients with abnormal uterine bleeding attending the gynaecology outpatient department (OPD) at Shri B. M. Patil Medical College, Vijayapura, Karnataka. Patient was thoroughly examined and then transvaginal sonography (TVS) was done after obtaining consent. This was followed by office hysteroscopy(OH) and endometrial biopsy was taken for histopathological examination. Data were gathered and examined and cost analysis of each procedure was done. Results: The most frequent presenting symptom was heavy menstrual bleeding (49.3%). For proliferative and secretory endometrium, the sensitivity of TVS was 81.48% and for the detection of polyps, endometrial hyperplasia, and submucous fibroid it was 45.45%, 42.86%, 100% respectively. The sensitivity of OH for detection of polyps, endometrial hyperplasia, and submucous fibroid which was 46.15%, 100%, 100% respectively. The p value was <0.05 which shows the statistical significance of both tests. TVS demonstrated low correlation for intracavitary diseases. OH was costlier when compared to TVS. Conclusions: TVS has more sensitivity and accuracy in detecting intramural pathologies. OH had showed greater diagnostic accuracy in identifying intra cavitary pathologies of uterus and doing intervention in the same setting.